Quantifying of thallium in Shilajit and its supplements to unveil the potential risk of consumption of this popular traditional medicine - Elham Kamgar; Joanna Zembrzuska; Wlodzimierz Zembrzuski; Massoud Kaykhaii (BMC Chemistry)
Abstract Shilajit, a natural substance used in traditional and modern medicine, has gained prominence as a vital component in dietary supplements. Concerns regarding its use in complementary medicine have arisen due to limited information regarding its composition. Considering thallium’s well-known toxicity, this study employs flow - injection differential-pulse anodic stripping voltammetry to accurately quantify thallium in natural Shilajit and Shilajit-based commercial supplements from various regions. The limit of detection and limit of quantification were determined as 6.58 × 10− 3 µg.mL− 1 and 1.98 × 10− 2 µg.mL− 1, respectively. Thallium contents were detected up to 0.226 µg.g− 1 in natural Shilajit, but mainly in the range of a few tenths of µg.g− 1. Thallium contents were found up to 0.5 µg.g− 1 in the supplements studied. Consumption of one pill of supplement, introduces up to 0.095 µg of Tl to the body. Notably, the concentration of thallium in some supplements was higher than in crude Shilajit, raising concerns about the potential health risks associated with long-term consumption. This study underscores potential health risks associated with thallium in both Shilajit and supplements. Regular monitoring and standardized testing are essential to ensure compliance with safe thallium limits, protecting consumers against potential thallium poisoning.